A Rare Presentation of Solitary Ocular Sarcoidosis / Kafil Akhtar ... [et al.] - Akhtar, Kafil Akhtar; Rehman, Suhailur; Haiyat, Sadaf; Waris, Abdul (Universiti Teknologi MARA Cawangan Selangor, 2021)
Ocular sarcoidosis leads to inflammation of the eye, manifesting as uveitis, scleritis and conjunctivitis with granuloma formation. It can involve any part of the eye and its adnexal tissues, and may result in complications like glaucoma and cataract. Ophthalmic manifestations of sarcoidosis can be isolated, or it may be associated with other organs of the body. The clinical presentation in ocular sarcoidosis is quite varied. Multi-disciplinary modality of treatment is required for both ocular and systemic manifestations of the disease. We report a rare presentation of solitary ocular sarcoidosis in a 42-year-old woman, who presented with complaints of painless left inner canthus swelling and blurry vision for 1 month.